The impact of flux and spacers on biofilm development on reverse osmosis membranes - Rice, Scott A. (2013)
Biofouling has been traditionally described as biofilm development on the membrane surface and leads to an increase in the required trans-membrane pressure (TMP). This study focuses on the impact of the feed channel spacer on the extent and nature of biofouling on the membrane. Experiments were conducted under conditions of constant flux with different hydrodynamics and biofouling was measured by TMP rise. In addition, biofilm development in the spacer-filled channel was monitored by confocal laser scanning microscope (CLSM) to both correlate the increase in TMP with the amount of biofilm development as well as to compare biofilm development on the feed channel spacer and the membrane. Faster TMP rise was observed under higher flux, lower crossflow, and higher salinity conditions. The presence of the feed channel spacer had a positive impact in terms of reduction of TMP rise, and no significant increase in channel pressure drop was observed during the experiments. In order to reconcile these observations with other studies that emphasize the role of spacer fouling, the scenarios likely to lead to predominance of membrane fouling or spacer fouling are discussed.